Blutungen unter NOAK - Koscielny, J.; Rutkauskaite, E. (Hämostaseologie, 2015)
The doses of these drugs are barely tested and the potential clinical thromboembolic risk must be taken into account. Despite the widespread use of NOAC (non vitamin-K dependent oral anticoagulants) and recommendations of regulatory agencies and first consensus meeting on handling the bleeding situation under NOAC, especially in hospitals without a large hemostatic focus, uncertainty still exists. In case of mild bleeding from a clinical perspective, the medical care of these patients and the delay of the next dose or discontinuation is advised. A special laboratory analysis is indicated i.e. in case of known higher grade liver and kidney failure, which can cause a prolonged elimination of NOAC. The administration of factor concentrates is not indicated in this situation. In case of moderate to severe bleeding, the primary measures focus on the stabilization of the heart and circulatory function and parallel on the treatment depending on the localization of the bleeding source. According to experience, mostly gastrointestinal bleeding occurs under the NOAC, which should be supplied endoscopically. In life-threatening bleeding in addition to the measures of hemodynamic stabilization usually a special haemostasis management is required, which should be mainly clinically oriented. After the assessment of bleeding predictor, the time of the last dose and the dose of NOAC should be learned, but other causes of bleeding, including Fibrinolysis, should be excluded or treated. Subsequently, routinely promptly rivaroxaban and/ or apixaban sensitive thromboplastin time (Quick’s value) and a thrombin time (thrombin- poor calibrator) for qualitative assessment can be carried out because only very few hospitals have specific tests (anti-Xa measurements, bovine thrombin), which could be promptly done. If there is a significant deviation from the normal range or to present preliminary value of particular patient, an effect of NOAC most likely exists. In life-threatening bleeding the use of factor concentrates (procoagulants) is indicated. The first-line therapy should be PPSB. Only in exceptional cases, especially when dabigatran is taken, the use of aPPSB (FEIBA®) for prompt haemostasis can be considered. The haemostasis should be always clinically estimated and not according to coagulation tests. The use of rFVIIa (Novo Seven®) shows different results in the bleeding therapy (reversal) under Dabigatran. The doses of these drugs are barely tested and the potential clinical thromboembolic risk must be taken into account.The current concepts of the newly developed antidotes are not clinically validated. First prospective, clinical registries have been started.
Keywords: Rivaroxaban; apixaban; dabigatran; anticoagulants; bleedings; bleeding risk; management of haemostasis; management of bleedings; PCC; FEIBA; antidots